Isolation and Identification of Triterpenoids from Flowers of Lawsonia inermis - Zhang, Jing; Liu, Jiang; Xu, Bin; Zhuang, Yan; Yosikawa, Masayuki; Yin, Bincan (Asian Journal of Chemistry, 2014)
A new oleanane-type triterpenoid, 2a, 3b-dihydroxyolean-18-en-28-oic acid (3) along with five known triterpenoids, b-sitosterol (1), oleanolic acid (2), crataegolic acid (4), alphitolic acid (5) and colosolic acid (6) were isolated from the flowers of Lawsonia inermis. Their structures were elucidated by spectroscopic analyses.